Análise dos parâmetros de sustentabilidade em dois campi de universidades federais: UNIFESP e UFSCar - Rodrigues, Suelen Cristiane (Universidade Federal de São Carlos, 2018)
The concern about sustainability, a comprehensive and multidisciplinary theme, it is effective in several areas of knowledge and in different sectors of society, since everyone, directly or indirectly, contributes to the degradation of the environment. Facing this responsibility, Public Institutions of Higher Education, which have an essential role in sustainable development, must invest in innovative solutions and seek the path of good practices to mitigate the environmental and socioeconomic damages caused by their infrastructure. Thus, the objective of the research is to evaluate the sustainability practices adopted by two Brazilian public universities. In this regard, a study of qualitative nature, with exploratory and descriptive character, was developed. The theoretical-conceptual background was made through the bibliographic review of the themes: sustainable development, universities within sustainable development, the sustainability practices contained in Brazilian universities, the Campus Verde concept and the restrictions of this model. There was the data gathering through the documentary analysis of the Institutional Development Plan, Infrastructure Master Plans, Sustainable Logistics Management Plan and Pedagogical Project of the universities. Furthermore, sustainability parameters were defined by means of a sketch deployment model composed of levels, based on the experiences of university campuses and the methodological proposals of analysis developed by researchers of the area. And for the analysis of practices with the F.O.F.A. application. The results indicated that the two universities planned actions in the established model categories, however, the superficiality of some proposals was verified, since gaps were identified between what was idealized in the variables and what effectively was implemented due to bureaucratic, budgetary and cultural barriers that present to be overcome. The study made it possible to understand that, despite the efforts undertaken by the evaluated institutions ,the sustainability practices are being gradually incorporated into the daily life of the university, and there are now specific and technical actions, such as practices for waste management in campuses and the research and extension projects that express the concern of the university with social issues, both actions directed by entrepreneurs committed to the environmental theme, indicating that there is a long way to be traversed for the effectiveness of sustainability in the university environment.
Analysis of the sustainability parameters in two campuses of federal universities: UNIFESP and UFSCar
Keywords: Sustentabilidade; Gestão Ambiental; Educação Ambiental; Sustainability; Environmental Management; Environmental Education; OUTROS